Trends in innovation management development - Krstić Milan; Skorup Ana; Lapčević Goran (Trendovi u Poslovanju)
In the background of technological progress generations of innovation can be found. Each of them is implemented as a process in which the idea of a change is born, and only after that the change is commercialized, this leading to its adoption by a wider range of users. Therefore, innovation management is organized as a set of management activities which results in innovation, thus gaining its importance. This paper briefly presents conducted theoretical desktop research, in order to determine the character of the innovative management development. The results suggest three key stages in the development of innovation management, namely: Management of individual technological innovation, Portfolio Innovation Management and Total Innovation management. The latest findings in the field of innovation management indicate that it is necessary to revise the concept of innovation in terms of its perception as an ecosystem. The paper points out the possible ways of further research in innovation management.